Tourism in East Caribbean Countries. (IMF Working Papers; Working Paper, 1988)
This paper studies recent developments in tourism in the East Caribbean countries (ECC) and reviews government policies to support tourism. The paper also presents a model to explain the movements of tourist arrivals to the region during 1970-86. The estimated model is used to project future tourist arrivals in the ECC.